(untitled) (Canadian Hematology Today, 2022)
Peripheral T-cell lymphomas (PTCL) are derived from post-thymic, mature T-cells and represent a clinically and biologically heterogeneous group of diseases. A common feature of the majority of PTCLs is a poor prognosis compared to their aggressive B-cell counterparts. Additionally, due to the rarity of the disease, the optimal therapy remains unknown. A large proportion of patients present with multiple poor risk factors as per the International Prognostic Index (IPI) and are rarely cured. The one exception is ALK positive anaplastic large cell lymphoma (ALCL), a group of diseases that has a much more favourable prognosis; however, those patients with ALCL and multiple IPI factors have a similar poor prognosis.